Carbon Dioxide Solubility Study of Piperazine Added Solvent - Parameswaran, Shaavesh Kumaran (Universiti Teknologi PETRONAS, 2016)
Carbon Dioxide is one of the primary greenhouse gases which are often emitted by human activities through combustion of fossil fuels for industrial process, energy and transportation. Excessive researches and studies are constantly being done in developing the best most possible solutions in CO2 removal. Post combustion capture and CO2 storage involves CO2 removal from natural gases to reduce emission in atmosphere .There are several approaches in CO2 absorption which are currently being used in the industry which are membrane separation by cryogenic distillation, solvents, using specifically amines and absorption .In this research the main objective is on using different type of amines with Piperazine to test for the solubility of CO2.